Asuhan Keperawatan Jiwa Pada Pasien DenganHalusinasi Pendengaran Di Wiswa FlamboyanRsj Prof. Hb. Saanin Padang - Suci Ramadani; Vivi Yuderna; Dwi Happy Anggia Sari; Ramaita . (CV. ITTC INDONESIA, 2026)
Hallucinations are sensory perception disorders characterized by the emergence of experiences felt without any real stimulation from the environment. Individuals with hallucinations can feel false sensations in the form of hearing, sight, smell, taste, or touch, even though there is no actual stimulus. This study aims to describe the application of psychiatric nursing care to patients experiencing auditory hallucinations at Prof. HB Saanin Mental Hospital Padang. The method used in this scientific paper is a case study with a nursing process approach that includes five stages, namely assessment, diagnosis, planning, implementation, and evaluation. The results of the assessment showed that the patient experienced signs and symptoms of hallucinations in the form of hearing whispering voices. The main nursing diagnosis was hallucinations with a co-diagnosis of self-care deficit (DPD). After nursing care was carried out, the patient was able to overcome self-care problems and was able to control hallucinations independently through the application of Implementation Strategies (SP), namely SP 1-4. These results indicate that the application of implementation strategies is effective in helping patients control hallucinations and improve self-care abilities. Therefore, it is hoped that this research can increase public understanding regarding the importance of mental health nursing care, thereby encouraging awareness in maintaining and preserving mental health and implementing behaviors that support the achievement of optimal psychological wellbeing in everyday life.